Electrochemical stability and degradation of commercial Rh/C catalyst in acidic media. (20th December 2021) - Smiljanić, Milutin; Bele, Marjan; Ruiz-Zepeda, Francisco; Šala, Martin; Kroflič, Ana; Hodnik, Nejc
Highlights: Electrochemical stability of Rh/C was studied by accelerated degradation protocols. IL-SEM and ex-situ TEM were used to study local nanoscale degradation mechanisms. EFC-ICP-MS was used to track Rh dissolution during degradation tests. Severe degradation of Rh/C occurs during cycling between 0.05 VRHE and 1.4 VRHE . Degradation of Rh/C occurs via dissolution followed by re-deposition. Abstract: Electrochemical stability of a commercial Rh/C catalyst has been studied in an acidic electrolyte by accelerated degradation protocols (ADP) which involved 5000 rapid voltammetric scans (1 V/s) in two potential regions: ADP1 was performed between 0.4 VRHE and 1.4 VRHE, while ADP2 was performed between 0.05 VRHE and 1.4 VRHE . Degradation of Rh/C was monitored by the changes in Rh electrochemical surface area (ECSA) and electrocatalytic activity for hydrogen evolution (HER) and oxygen reduction (ORR). Rh/C catalyst was particularly stable during ADP1 showing only a minor loss of ECSA, while its electrocatalytic activity for HER and ORR was practically unaffected, which was further corroborated with identical location SEM (IL-SEM) imaging. In the case of ADP2, severe degradation of Rh/C occurred followed by substantial decay in its electrocatalytic activity. Coupling of the electrochemical flow cell (EFC) with ICP-MS revealed much higher Rh dissolution in ADP2 than in ADP1. IL-SEM in combination with ex-situ TEM imaging showed that degradation of the Rh/C sample is not homogeneous during ADP2, as dissolution prevails on certain locations, while dissolution followed by re-deposition occurs on others. According to the results obtained in this work, Rh/C catalysts are exceptionally sensitive to the sudden potential jumps between particularly low and high values. Graphical abstract: Image, graphical abstract